2021
DOI: 10.3390/ijms22041560
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of TLR4 and TLR8 in the Innate Immune Response against Mycobacterium Tuberculosis

Abstract: The interaction and crosstalk of Toll-like receptors (TLRs) is an established pathway in which the innate immune system recognises and fights pathogens. In a single nucleotide polymorphisms (SNP) analysis of an Indian cohort, we found evidence for both TLR4-399T and TRL8-1A conveying increased susceptibility towards tuberculosis (TB) in an interdependent manner, even though there is no established TLR4 ligand present in Mycobacterium tuberculosis (Mtb), which is the causative pathogen of TB. Docking studies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…The relationship between IRF3 and TLRs has been well documented with several studies reporting an interaction between TLR4/TRIF/IRF3 signaling 44–46 . IRF3 has been implemented in the development of insulin resistance and suggested as a possible therapeutic target 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between IRF3 and TLRs has been well documented with several studies reporting an interaction between TLR4/TRIF/IRF3 signaling 44–46 . IRF3 has been implemented in the development of insulin resistance and suggested as a possible therapeutic target 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between IRF3 and TLRs has been well documented with several studies reporting an interaction between TLR4/TRIF/IRF3 signaling. 44 , 45 , 46 IRF3 has been implemented in the development of insulin resistance and suggested as a possible therapeutic target. 22 The manipulation of TLRs that lay upstream of IRF3 was found to influence insulin resistance in murine adipocytes whereas the knockdown of IRF3 abolished insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-type specific differences in the expression level and utilization of TIRAP in TLR8 signaling should also be addressed. Furthermore, SNPs in TIRAP are associated to the incidence and severity of several diseases, such as tuberculosis, HIV, and systemic lupus erythematosus (SLE) [ 18 ] as well as infections/diseases in which TLR8 is likely to play a role [ 63 , 64 , 65 ]. Thus, understanding the contribution of TIRAP to the fine-tuning of TLR8 signaling might be of significant clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells can be activated by the interaction between TLR4 and Mtb components, such as secretory protein (Rv0335c), lipomannan (LM), HSPs 60, and 65 [ 65 , 102 ]. In a recent study, Thada et al found that TLR4 can bind TLR8 to recognize TLR8 ligands produced by Mtb [ 103 ]. In chronic Mtb infection, it has been demonstrated that macrophage recruitment, pro-inflammatory responses, and the ability to eliminate mycobacteria were impaired in TLR4 deficient mice [ 104 ].…”
Section: Tlr2 Function In Immune Responses To Mycobacterial Infectionmentioning
confidence: 99%